Drug‐induced liver injury in a chronic hepatitis C patient treated by peginterferon, ribavirin and simeprevir. Issue 10 (18th February 2015) - Okajima, Akira; Yamaguchi, Kanji; Taketani, Hiroyoshi; Hara, Tasuku; Ishiba, Hiroshi; Seko, Yuya; Nishimura, Takeshi; Nishikawa, Taichiroh; Fujii, Hideki; Moriguchi, Michihisa; Mitsuyoshi, Hironori; Sumida, Yoshio; et al.
Abstract : A 56‐year‐old male patient with chronic hepatitis C was treated with pegylated interferon (PEG IFN)‐α‐2b and ribavirin (RBV) for 72 weeks in 2006. The patient achieved an early virological response (EVR); however, hepatitis C relapsed 12 weeks after discontinuation of PEG IFN and RBV. In 2012, the patient was treated with a PEG IFN/RBV/telaprevir combination therapy. After 5 days of treatment, he suffered from a telaprevir‐associated skin rash on his body and four limbs. He chose to be treated with PEG IFN and RBV until 60 weeks. He again achieved EVR but no sustained virological response. In 2014, he was treated with PEG IFN/RBV/simeprevir combination therapy. He achieved rapid virological response, but after 6 weeks of therapy, a striking elevation of serum aminotransferase level was recorded with no accompanying skin rash; he was admitted to our hospital. PEG IFN/RBV/simeprevir was stopped, but sodium valproate (400 mg/day), which had been administrated for more than 10 years to prevent epilepsy was continued. Liver biopsy revealed typical features of drug‐induced liver injury. After stopping PEG IFN/RBV/simeprevir, serum aminotransferase levels soon returned to the normal range. We diagnosed this case to be simeprevir‐induced hepatitis clinically and histologically. Physicians need to stay alert to the possibility of drug‐induced liver injury in using simeprevir.